Employment Protection and Sickness Absence - Martin Olsson (Research Institute of Industrial Economics (IFN), 2007)
An exemption in the Swedish Employment Security Act (LAS) in 2001 made it possible for employers with a maximum of ten employees to exempt two workers from the seniority rule at times of redundancies. Using this within-country enforcement variation, the relationship between employment protection and sickness absence among employees is examined. The average treatment effect from the exemption is found to decrease sickness absence by more than 13 percent at those establishments that were treated relative to those that were not and this was due to a behavioral, rather than a compositional, effect. The results suggest that the exemption had the largest impact on shorter spells and among establishments with a relatively low share of females or temporary contracts.
Keywords: I19; J63; J88; 330; Employment Protection; Sickness Absence; Economic Incentives; Kündigungsschutz; Krankheit; Fehlzeit; Ökonomischer Anreiz; Wirkungsanalyse; Schweden